Characterization of Heat Tolerance in Two Apple Rootstocks Using Chlorophyll Fluorescence as a Screening Method - Ines Mihaljević; Marija Viljevac Vuletić; Vesna Tomaš; Dominik Vuković; Zvonimir Zdunić (Agronomy)
High temperature has an adverse effect on apple production worldwide. Photosynthesis is a process especially vulnerable to heat stress, which can reduce photosynthetic efficiency, plant growth, development, and ultimately yield. Although the effects of heat stress on apples have been partially examined, the photochemical reactions and heat tolerance of specific rootstocks have still not been sufficiently investigated. Identification of rootstocks with better photosynthetic performance and adaptation to heat stress enables the selection of rootstocks, which could contribute to stable yields and good fruit quality even at elevated temperatures. In this study, chlorophyll a fluorescence (ChlF) induction kinetics was used to investigate the heat tolerance between two apple rootstocks (M.9 and G.210). In addition, we employed lipid peroxidation measurements, hydrogen peroxide quantification, proline content, and total phenolic and flavonoid assessments. Analysis of chlorophyll fluorescence parameters and OJIP curves (different steps of the polyphasic fluorescence transient; O–J–I–P phases) revealed significant differences in their responses, with higher values of the PIABS parameter indicating better PS II stability and overall photosynthetic efficiency in M.9 rootstock. The higher contents of chlorophyll, carotenoids, proline, and significant increase in the accumulation of phenolics, and flavonoids in this rootstock also contributed to its better adaptation to heat stress. Oxidative stress was more pronounced in G.210 through higher H2O2 and MDA levels, which could point to its lower capacity to adjust to heat stress conditions. This research can provide a scientific basis for further breeding programs and growing plans due to climate change and the occurrence of extremely high temperatures.